PENYULUHAN HUKUM BAGI SISWA DAN SISWI SMAN 3 TAMBUN SELATAN TERKAIT UPAYA PENCEGAHAN KEKERASAN SEKSUAL DI LINGKUNGAN SEKOLAH - Fransiska Novita Eleanora; Dwi Seno Wijanarko; Fanny Afifah; Pramesty Anindya Putri; Sulistiawati Sulistiawati; Salma Salsabila; Sony Ryan Pradana; Maulana Fahrul Hidayat; Kevin Louis; Aimee Malca Luwinanda (Jurnal Edukasi Pengabdian Masyarakat, 2023)
The phenomenon of acts of sexual violence is increasing rapidly which can also be in the form of sexual harassment which often makes children become victims because children are very weak and vulnerable to actions or actions in the form of harassment and sexual violence. The occurrence of sexual violence can occur anywhere and anytime, both in the environment where children live and also in the school environment where children get knowledge and education for the future, but instead children get actions that violate decency and result in trauma and depression. and stress which results in or has the effect of decreasing enthusiasm for learning, silence, sadness or even contemplating a lot and of course the child is not as cheerful as usual. Therefore, so that children or students do not become perpetrators or even victims of acts of harassment and even sexual violence, it is necessary to prevent efforts in the form of increasing understanding of the extent of sexual harassment and violence that students need to know so that they can respond and protect themselves. to always be vigilant and careful not to fall victim.